Evaluating Gibberellic Acid-Induced Seed Dormancy Release in Rice (Oryza sativa L.) for Enhanced Germination - Del Rosario, Mirasol; Valdez, Manolo (Journal of Interdisciplinary Perspectives, 2025)
Seed dormancy is a significant challenge in rice production, leading to uneven and poor germination rates. This study examines the effectiveness of gibberellic acid (GA3) in enhancing rice seed germination by alleviating seed dormancy. The experiment was conducted from April to May 2024 at Barangay Mabini, Santo Domingo, Nueva Ecija, using a Completely Randomized Design (CRD) with six treatments (Control, 50 ppm, 75 ppm, 100 ppm, 150 ppm, and 200 ppm GA3) and three replications. The primary objectives were to assess the impact of varying GA3 concentrations on seed dormancy release in an inbred rice variety (NSIC Rc 160), determine the optimal concentration for maximum germination rates, and compare the germination and seedling emergence performance of GA3-treated seeds with that of untreated seeds. The study analyzed critical germination data such as percent germination, and percent of seedling emergence, time to 10% germination and emergence (T10), mean germination and emergence time (T50), time to 90% germination and emergence (T90), and mean spread of germination and emergence time (T90-T10). The results showed that GA3 treatments at up to 150 ppm significantly increased germination rates compared to the control. The 50 ppm GA3 treatment was remarkably efficient, resulting in a 100% germination rate in one setup and the fastest T10. Higher concentrations (200 ppm) were shown to inhibit germination while significantly increasing T10, T50, and T90. Optimal germination enhancement was observed at concentrations ranging from 50 to 150 ppm, with 50 ppm showing the most consistent improvement across all parameters. The study also found that GA3 concentrations significantly improved the uniformity of germination and emergence times in rice cultivation. The 75 ppm treatment improved germination uniformity slightly, whereas higher concentrations (100 and 200 ppm) resulted in a slight increase in spread. The ideal concentration for increasing emergence uniformity was around 150 ppm. This study demonstrates that optimal GA3 concentrations can effectively break seed dormancy and enhance rice germination rates, providing valuable insights for improving rice production and food security. These results show that GA₃ can improve germination performance and seedling uniformity by breaking dormancy. The use of ideal GA₃ concentrations has the potential to enhance seed technology and promote sustainable rice production by facilitating more effective rice establishment.